Sexual relations between adults and children in eighteenth-century Venice - Wolff, Larry (Acta Histriae, 2007)
This paper considers several cases that came before Venetian tribunals in the eighteenth century concerning sexual relations between adults and children. The paper will attempt to analyye the precise (or imprecise) nature of the criminality involved in such relations in the eighteenth century, and the particular concerns and procedures of Venetian law in addressing such cases. Analysis will consider to what extent modern terms such as 'deviance' and 'abuse' are relevant for understanding the meaning of such cases in their eighteenth-century contexts, and will address the significance of the Enlightenment for emphasizing particular categories of criminality. Further attention will be addressed to the concept of eighteenth-century libertinism, and its implications for sexual relations between adults and children, and also to the evolution of early modern ideas about the special significance of childhood. The disciplinary framework of the paper will consider the dimensions of legal, social, and cultural history
Keywords: Benetke; child; otroci; otroštvo; spolni zločini; Venice; zlorabe